Anisotropic diffusion of Fe ions in Fricke-XO-Pluronic F-127 and Fricke-XO-gelatine 3D radiotherapy dosimeters. (20th July 2021) - Dudek, M; Piotrowski, M; Maras, P; Jaszczak, M; Kozicki, M
Abstract: A new radiochromic dosimeter was examined with Raman spectroscopy and an optical approach for assessment of 3D dose distribution integrity. The acronym of the dosimeter is Fricke-XO-Pluronic F-127, where XO denotes xylenol orange; Pluronic F-127 is a copolymer matrix of poly(ethylene oxide)- block -poly(propylene oxide)- block -poly(ethylene oxide), and the dosimeter contains the components of a Fricke dosimetric solution. Two dosimeter samples in cuvettes were partially irradiated such that a radiation dose was absorbed at the bottom of the cuvettes. After irradiation, one sample was stored upside down such that the irradiated part was at the top and another one was stored with the irradiated part at the bottom. Two diffusion coefficients of ferric ion complexes with XO ([XO-Fe] +3 ) were calculated. They were compared with those for similar dosimeter, however with gelatine matrix instead of Pluronic F-127. The results obtained indicate an impact of the gravitational force on the diffusion of [XO-Fe] +3 ions over time after irradiation and thus a possibility of severely undermining the integrity of a dose distribution in irradiated dosimeter. The conclusions drawn suggest the necessity of examination of different 3D Fricke dosimeter compositions for anisotropic diffusion of ferric ions.